Morphological Changes Occurring in the Gastric Mucosa of Adult Outbred White Rats under the Influence of Anti-Inflammatory Drugs - Norbekovich , Toshmamatov Bakhtiyor; Eshmamatovna, Djumanova Nargiza; Umarovnas, Sultonova Zarina (American Journal of Bioscience and Clinical Integrity, 2026)
Anti-inflammatory drugs are widely used in medical practice; however, their effect on the gastric mucosa remains a subject of active research. This study aimed to investigate morphological changes in the gastric mucosa of adult outbred white rats under the influence of anti-inflammatory drugs. Experimental animals were administered anti-inflammatory agents, after which histological and morphometric analyses of the gastric mucosa were performed. The results revealed structural alterations in the gastric mucosa, including changes in glandular cells and mucosal integrity, indicating a drug-induced impact on gastric tissue. These findings contribute to a better understanding of the morphological effects of anti-inflammatory drugs on the stomach and may be useful for improving the safety of pharmacological therapy.